2017
DOI: 10.1101/134213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active trachoma cases in the Solomon Islands have varied polymicrobial community structures but do not associate with individual non-chlamydial pathogens of the eye

Abstract: Active trachoma cases in the SolomonAll rights reserved. No reuse allowed without permission.(which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/134213 doi: bioRxiv preprint first posted online May. 11, 2017; Running header: Microbial correlates of active trachoma in the Solomon Islands 2 Abstract 31 32

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
(68 reference statements)
1
10
1
Order By: Relevance
“…The World Health Organization guidelines for implementing mass drug administration (MDA) are based largely on TF prevalence. We have previously argued that whilst the Solomon Islands has sufficiently prevalent clinical signs (TF) of trachoma to qualify for implementation of MDA, the prevalence of infection and trichiasis [ 3 , 5 ], as well as severe scarring and serological signs of prior infection [ 6 ] are all too low to suggest that clinical diagnosis with TF has the necessary specificity to be used as an indicator of need for intervention in this population. By showing that the transcriptional profile of TF ( Ct uninfected) cases in the Solomon Islands share some, but not all, the components of typical trachoma responses seen elsewhere, the current findings add to those of our previous studies to suggest that the majority of TF disease we observe there is not related to Ct .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The World Health Organization guidelines for implementing mass drug administration (MDA) are based largely on TF prevalence. We have previously argued that whilst the Solomon Islands has sufficiently prevalent clinical signs (TF) of trachoma to qualify for implementation of MDA, the prevalence of infection and trichiasis [ 3 , 5 ], as well as severe scarring and serological signs of prior infection [ 6 ] are all too low to suggest that clinical diagnosis with TF has the necessary specificity to be used as an indicator of need for intervention in this population. By showing that the transcriptional profile of TF ( Ct uninfected) cases in the Solomon Islands share some, but not all, the components of typical trachoma responses seen elsewhere, the current findings add to those of our previous studies to suggest that the majority of TF disease we observe there is not related to Ct .…”
Section: Resultsmentioning
confidence: 99%
“…From the whole population sample, three subsets of specimens were selected for the microarray-based gene expression profiling experiment. Group N ( n = 7) were children who had neither TF, nor Ct infection [ 3 ] , nor any of other common ocular infections (as listed in the introduction) [ 6 ]. Group D ( n = 7) were children who did have TF, but had neither Ct nor any of the other infections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Solomon Islands investigating this pattern suggest that the cause may not be bacterial. 36 Another marker of interest for assessing severity of disease is intense inflammation. Intense inflammation is consistently demonstrated to be associated with incidence and progression of scarring in longitudinal studies and prevalence and load of Ct infection are higher in people with TI than in those with TF.…”
Section: Discussionmentioning
confidence: 99%
“…This may affect the presence of other organisms in the conjunctiva. Indeed, although conflicting evidence exists, studies of human trachoma have reported that chlamydial disease is associated with a decrease in microbial richness and diversity compared to healthy controls [31,32]. Innate immune responses form a key part of the host response to chlamydial infection and, although only speculation, it is possible that upregulation of these processes at the mucosal surface may inadvertently impact on infection by other organisms such as the novel virus detected in this study [30].…”
Section: Discussionmentioning
confidence: 73%